Managing Variety in Configure-to-Order Products - An Operational Method - Myrodia, Anna; Hvam, Lars (International Journal of Industrial Engineering and Management, 2014)
Companies producing customized products tend to increase the variety of their product portfolio, in order to fulfill the demand of their customers and align their strategies with those of competitors. However, the profitability of product families may vary greatly. The purpose of this paper is to develop an operational method to analyze profitability of Configure-To-Order (CTO) products. The operational method consists of a four-step: analysis of product assortment, profitability analysis on configured products, market and competitor analysis and, product assortment scenarios analysis. The proposed operational method is firstly developed based on both available literature and practitioners experience and subsequently tested on a company that produces CTO products. The results from this application are further discussed and opportunities for further research identified. Article history: Received (25.08.2014); Revised (19.10.2014); Accepted (20.11.2014)